Association between Silica Dust Exposure and Serum Transforming Growth Factor-β1 in Stone Quarry Workers - I Putu Eka Krisnha Wijaya; Ida Bagus Ngurah Rai; I Putu Andrika (Jurnal Penyakit Dalam Indonesia)
Introduction. Silicosis is a disease that most often occurred as a result of silica dust exposure. Silica dust particles will stimulate alveolar macrophages to secrete proinflammatory mediators for fibroblast proliferation and collagen deposition. TGF-ß1 is one of the most extensively involved mediators in the development of fibrosis. To date, several studies have not shown consistent results regarding the association between silica dust exposure and TGF-β1. This study examined silica dust exposure and serum TGF-β1, which aims to determine the risk of silicosis in stone quarry workers.